Ba virtual and inter-organizational evolution: a case study from a EU research project. Issue 4 (11th July 2016) - Bartolacci, Chiara; Cristalli, Cristina; Isidori, Daniela; Niccolini, Federico
Abstract : Purpose: Taking Nonaka's SECI model as the main reference, this paper aims to offer reflections on the virtual evolution of ba, the places for knowledge creation. Indeed, looking at the current scenario, widening the knowledge spiral to the inter-organizational epistemological level is inevitable. To this aim, information technology tools and virtual communities can establish effective interactions to exchange knowledge, making ba evolve congruently. Design/methodology/approach: The paper takes the exemplary case of a platform developed during a European research project called "BIVEE: Business Innovation in Virtual Enterprise Environments". The investigative approach chosen is participatory action research (PAR), with two researchers conducting PAR in real time, and two others involved ex post . Findings: The paper shows that the virtual evolution of ba can lead the SECI model towards an inter-organizational level. Moreover, through a learning history, it describes how all the phases of the SECI process, even the Socialization one, can take place or be supported in virtual spaces. Research limitations/implications: Taking into account just one single exemplary case study provides a rich, contextualized understanding of phenomena, while allowing only some theoretical generalizations. Originality/value: This paper contextualizes the SECI model within a Web platform for open innovation, to investigate whether the knowledge creation process can take place entirely within a virtual environment linking subjects from different organizations. In so doing, it applies the SECI model to the phases of the innovation process, called waves.